1=3(x-4)-(x-9)

Simple and best practice solution for 1=3(x-4)-(x-9) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 1=3(x-4)-(x-9) equation:


Simplifying
1 = 3(x + -4) + -1(x + -9)

Reorder the terms:
1 = 3(-4 + x) + -1(x + -9)
1 = (-4 * 3 + x * 3) + -1(x + -9)
1 = (-12 + 3x) + -1(x + -9)

Reorder the terms:
1 = -12 + 3x + -1(-9 + x)
1 = -12 + 3x + (-9 * -1 + x * -1)
1 = -12 + 3x + (9 + -1x)

Reorder the terms:
1 = -12 + 9 + 3x + -1x

Combine like terms: -12 + 9 = -3
1 = -3 + 3x + -1x

Combine like terms: 3x + -1x = 2x
1 = -3 + 2x

Solving
1 = -3 + 2x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-2x' to each side of the equation.
1 + -2x = -3 + 2x + -2x

Combine like terms: 2x + -2x = 0
1 + -2x = -3 + 0
1 + -2x = -3

Add '-1' to each side of the equation.
1 + -1 + -2x = -3 + -1

Combine like terms: 1 + -1 = 0
0 + -2x = -3 + -1
-2x = -3 + -1

Combine like terms: -3 + -1 = -4
-2x = -4

Divide each side by '-2'.
x = 2

Simplifying
x = 2

See similar equations:

| 7(x-8)-8(x-7)=x+7-(x-2) | | 13j+-9j+15=3 | | 6p-2-3p=17 | | 3n+1-16-n=20 | | 16v+-4v+-14=10 | | 8x+8=6x+44 | | 14x=x^2 | | 2y-9=10y+55 | | 8x-(2x-8)=62 | | 4a-5b=5 | | 5x-(x+4)=5+4(x-2) | | a=5 | | -14v+7=-7 | | 19y+-y+2y=-20 | | 4x-80=180 | | 8+8y=-6+3y | | 5x-9y=2 | | 4x-80=120 | | y+15=-2(x-15) | | 10x-2(x+4)=8(x-2)+6 | | 8v+6=4v-2 | | x^2+1x+10= | | -9(-21)= | | (x^4+5y^5)(x^4-y^5)= | | x+(x+5)(-2)= | | (3v+5)(3c-5)= | | x+2v=w | | (5c-3)(6c-5)= | | R=-0.408 | | x-4(x+2)= | | 4x^3y+16x^2y+12xy= | | -3m=4.2 |

Equations solver categories